Thyme Essential Oil: Uses, Applications and Extraction - Tejada Ortigoza, Viridiana (Nova Science Publishers, 2018)
Thyme has been used for its medicinal effects for thousands of years. Its culinary and cosmetic applications have impacted the industry not only as a flavour or aroma ingredient but also as an antimicrobial, antioxidant, antitussive, spasmolytic, and antitumoral ingredient, to mention some. The importance of thyme essential oil, extracts, and components (thymol and carvacrol) relies on these technological and physiological functionalities for the food, biotechnology, and pharmaceutical industries, thus increasing its economic impact. Thermal treatments such as hydrodistillation or steam distillation have been performed to obtain thyme essential oil, extracts or components. However, these processing conditions, might affect both the physiological and technological features, mainly due to the high temperatures used during the treatments. Recent research has been focused on the use of alternative extraction processes. Ultrasound or microwave, have been employed to assist the extraction, improving the yield and maintaining the performance of the compounds. A critical insight into the advances in functionality and extraction processes of thyme essential oil, extracts, and main components is described in this chapter.